Maintenance of Karo Language Among Teenagers in Tanjung Merahe Village, Selesai District, Langkat Regency (Socio- Linguistic Study) - Melinta Br PA; Siti Aisyah Hanim; Maulidawati (Global Action and Education for Society, 2026)
This study aims to analyze the factors influencing the maintenance of the Karo language among teenagers in Tanjung Merahe Village based on Downes’ theory, which categorizes language use into four domains: family, friendship, activities, and motivation. This research employed a qualitative descriptive method with in-depth interviews conducted with selected informants. The findings reveal that in the family domain, six factors contribute to maintaining the Karo language at home: intentional teaching of the Karo language to children, intergenerational interaction, the use of Karo during family events, a home environment predominantly speaking Karo, and the instillation of Karo cultural values from an early age. In the friendship domain, six factors support the use of the Karo language: interaction with peers who speak Karo, the habit of conversing in public spaces, use of Karo within youth communities, peer influence in traditional settings, use of Karo in certain social media contexts, and role modeling by community leaders in language use. In the activity domain, two key factors were identified: the predominant use of Karo in traditional ceremonies and the involvement of teenagers in various cultural activities such as traditional ceremonies, arts, and Karo traditional music.In the motivation domain, six factors indicate the drive to maintain the Karo language: pride in using the Karo language, the desire to highlight Karo identity in front of outsiders, awareness of the importance of language preservation, commitment to using Karo in various situations, the intention to pass the language to future generations, and support from the village government through cultural preservation programs.